Використання абстрактного та казуїстичного прийомів при конструюванні кримінальних правопорушень у сфері свободи слова та журналістської діяльності - Пахнін, М. Л.; Pakhnin, M. L.; Микола Пахнін (Європейські перспективи. - 2021. - № 4. – С. 90-95, 2021)
Розглянуто питання конструювання диспозицій норм про кримінальні правопорушення у сфері свободи слова та журналістської діяльності. Досліджено особливості застосування казуїстичного прийому законодавчої техніки, розглядаються тенденції у регламентації складів правопорушень проти законної професійної діяльності журналістів.

The article considers the issues of constructing dispositions of norms on criminal offenses in the field of freedom of speech and journalistic activity, examines the peculiarities of the application of casuistic methods of legislative technique, trends in the regulation of offenses against lawful professional activity of journalists. The analysis of casuistry and abstractness in the description of the dispositions of criminal law, including those related to the obstruction of the lawful professional activity of journalists, revealed the following trends. In many cases, without taking into account the peculiarities and traditions of national legislation, the legislator tries to transfer (copy) the provisions of international acts to the domestic regulatory field.In other cases, the legislator simply tries to list the most typical examples of criminal behavior and “frames” it with instructions “as well as other socially dangerous acts” or the presence of criminal consequences, thus bringing the content of public danger to the level necessary for criminalization. In general, it is concluded that it is necessary to revise the legislation on liability for obstructing the legitimate professional activities of journalists and to develop simple, clear, logical small dispositions that establish the characteristics of offenses in the field of freedom of speech and journalism.

Рассмотрены вопросы конструирования диспозиций норм об уголовных правонарушениях в сфере свободы слова и журналистской деятельности. Исследованы особенности применения казуистического приёма законодательной техники, рассматриваются тенденции в регламентации составов правонарушений против законной профессиональной деятельности журналистов.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; професійна діяльність журналістів; professional activities of journalists; профессиональная деятельность журналистов; свобода слова; freedom of speech; кримінальне законодавство; criminal law; уголовное законодательство; кримінальне правотворення; criminal legislation; перешкоджання законній професійній діяльності журналістів; hindering the legitimate professional activity of journalists; препятствование законной профессиональной деятельности журналистов; казуїстичний прийом; casuistic method; казуистический прием; норми права; законодавча техніка; legislative machinery; законодательная техника; абстрактний прийом; abstract reception; абстрактный прием